USAHA MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PKN MELALUI PEMBELAJARAN KOOPERATIF TIPE ROLE PLAYING DI KELAS VI SDN WARUNGKETAN SITURAJA - Ade Ratna Dewi Suminar (Jurnal Edukasi Sebelas April, 2019)
The problems in this study are: 1) What is the process of implementing learning by using role playing learning models in Civics in the sixth grade at SDN IV Parepare City, Enrekang Regency? From the formulation of the problem, the research aims: 1) To find out information about the process of implementing learning by using role playing models in improving the learning outcomes of Civics in class VI SDN Warungketan, Situraja District, Sumedang Regency. The research approach is a qualitative approach with the type of research is classroom action research. This study focuses on the process of student and teacher activities by applying cooperative learning to role playing types and focusing on student learning outcomes after the implementation of learning by using role playing cooperative learning models. The study was conducted at SDN Warungketan, Situraja Subdistrict, with subjects being teachers and sixth grade students at SDN Warungketan, Situraja Subdistrict, Sumedang District, totaling 30 people, consisting of 16 men and 14 women. The research procedures and design used are: planning, action implementation, observation and reflection. From the implementation obtained data collected by observation techniques, learning achievement tests and documentation. Then the data is analyzed and processed qualitatively. Learning outcomes obtained from the level of success of students who have successfully reached the KKM school, which tends to increase, respectively: cycle I, sufficient qualifications, and cycle II, good qualifications. The conclusion of the research is that there is an increase in student learning outcomes in Civics through cooperative learning role playing types in class VI SDN Warungketan, Situraja District.